1995
DOI: 10.1111/j.1432-1033.1995.390_b.x
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acids and Fibrates are Potent Inducers of Transcription of the Phosphenol pyruvate Carboxykinase Gene in Adipocytes

Abstract: Cytosolic phosphoPnolpyruvate carboxykinase (PEPCK) plays a critical role in adipose tissue glyccroneogenesis. We havc previously shown that transcription of the PEPCK gene was stimulated by isoprend i n e and relinoic acid in 3T3-E'442A adipocytes. We. also showed that oleate increased PEPCK mRNA. Here, we analysed the effect that fatty acids of various chain lengths and unsaturation degrces exerted on PEPCK gene expression in 3T3-F442A adipocytes. Whcn maintained in scrum-free, glucose-free medium, different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
34
1
2

Year Published

1997
1997
2013
2013

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 45 publications
11
34
1
2
Order By: Relevance
“…As expected, a strong correlation was also shown between the glyceroneogenic flux of the tissue and the release of NEFA in the incubation medium. As a consequence, we observed a large decrease in plasma NEFA concentration in agreement with the role that glyceroneogenesis is playing in G3P synthesis required for fatty acid esterification after a high-fat or high-protein carbohydrate-free diet and for reesterification during fasting [36,37]. According to the minor role of glycerol phosphorylation in this process, we could not detect any variation in glycerol release whether rats were treated with rosiglitazone or not, in agreement with our previous studies, in which either a very mild decrease or no variation in glycerol release was observed [18].…”
Section: Discussionsupporting
confidence: 84%
“…As expected, a strong correlation was also shown between the glyceroneogenic flux of the tissue and the release of NEFA in the incubation medium. As a consequence, we observed a large decrease in plasma NEFA concentration in agreement with the role that glyceroneogenesis is playing in G3P synthesis required for fatty acid esterification after a high-fat or high-protein carbohydrate-free diet and for reesterification during fasting [36,37]. According to the minor role of glycerol phosphorylation in this process, we could not detect any variation in glycerol release whether rats were treated with rosiglitazone or not, in agreement with our previous studies, in which either a very mild decrease or no variation in glycerol release was observed [18].…”
Section: Discussionsupporting
confidence: 84%
“…This finding indicates that PUFA-mediated regulation of adipose tissue gene expression would not necessarily need extra-adipose factors. For instance, phosphoenolpyruvate carboxykinase (EC 4.1.1.32) mRNA was strongly induced (about tenfold) by fibrates and DHA compared with oleic acid in adipocyte cell line 3T3-F442A, and the role of a PPAR in fatty acid signalling has been postulated (Antras-Ferry et al 1995). It is interesting to note that DHA is a strong activator of PPARγ2, which is a transcription factor specifically expressed in adipose tissue.…”
Section: Effect Of Polyunsaturated Fatty Acids On Adipose Tissue Genementioning
confidence: 99%
“…Nuclei were prepared essentially as described by Shapiro (26) except that they were purified on a 2 M sucrose cushion. Briefly, the nuclear pellet resuspended in 2 M sucrose was layered on a 2 M sucrose cushion and then centrifuged at 40,000 rpm in an SW41 rotor at 4°C for 1 h. Nuclear run-on transcription was assayed as described by AntrasFerry et al (27). About 50 ϫ 10 6 cpm were hybridized per membrane.…”
Section: Methodsmentioning
confidence: 99%